Heart Rate Estimation by PCA with LSTM from Video-based Plethysmography Under Periodic Noise - Chetsadaporn Traivinidsreesuk; Nutcha Yodrabum; Irin Chaikangwan; Taravichet Titijaroonroj (My University, 2022)
A remote photoplethysmography (rPPG) analysis can extract vital signs from the source video, including heart rate estimation. One of the problems of heart rate estimation is periodic noise embedded in the source video. It is difficult for an rPPG analysis to discriminate between vital signal information and noise, increasing prediction error. To alleviate this problem, this paper used principal component analysis (PCA) to extract rPPG signals from the input video before forwarding the signal to Long Short Term Memory (LSTM) to estimate heart rate. The experimental results show that, among discrete Fourier Transform method, neural networks, and neural network with LSTM, the proposed method accomplished a much lower MAEP at 15.05, 13.90, and 17.90 in the cases of overall, with no periodic noise, and with periodic noise, respectively.
Keywords: Non-Invasive Vital Sign Monitoring; Heart Rate Variability and Autonomic Control; ECG Monitoring and Analysis